Robert J. Chalmers:: Pioneer Surficial Geologist - Brookes, Ian (Geoscience Canada, 2008)
SUMMARY Most Quaternary geologists working in Atlantic Canada view Robert J. Chalmers’ investigations of the surficial geology of New Brunswick for the Geological Survey of Canada (GSC) as seminal contributions. Yet, the fullest biographical information available for Chalmers is a 7-page typescript by E.R. Faribault of the GSC, held at Natural Resources Canada Library in Ottawa. Therefore, it appeared necessary to bring Chalmers’ little-known life, and the variety of his surficial geologic investigations, into the mainstream. Lists of Chalmers’ published works in GSC reports and in periodicals are compiled from all available sources.